IDENTIFIKASI SIFAT FISIK DAN KIMIA TANAH PADA LAHAN PERSAWAHAN DI KECAMATAN KOTAMOBAGU SELATAN - Dimas Ajie Saputra; Sandra E. Pakasi; Verry Ch. Warouw (Universitas Sam Ratulangi, 2020)
ABSTRACTThe purpose of this study is to determine the physical and chemical properties of the soil on thepaddy fields in the District Kotamobagu Selatan. This research was conducted in the month of Octoberuntil November 2019. The method used is survey method, namely by direct observation in the field anddoing analysis. Soil samples taken at the 41 point spread on a land area of rice fields amounted to1318.07 ha. . Parameters observed were Soil Texture (method of Kang Biaw Tjwan), soil pH (pHmeter), C-organic matter (method of Walkley and Black), Nitrogen (method of Kjedhal), Phosphorus(method of Bray I) and Potassium (method of Bray I). Research data analysis using descriptive analysis.The results showed that, soil physical and chemical properties in paddy fields in the DistrictKotamobagu Selatan are as follows physical properties of the soil have a clay texture dusty, andchemical properties of the soil that consists of : a pH within the criteria of neutral, C-organic is in thecriteria high to low, the nitrogen criteria of low to very low, phosphorus is in the criteria is and thepotassium is on the kiteria was.Keywords: physical properties, chemical properties, paddy field,